2011
DOI: 10.1007/s10904-011-9588-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Modeling of the Morphology and Properties of Segmented Silicone-Urea Copolymers

Abstract: Molecular dynamics and mesoscale dynamics simulation techniques were used to investigate the effect of hydrogen bonding on the microphase separation, morphology and various physicochemical properties of segmented silicone-urea copolymers. Model silicone-urea copolymers investigated were based on the stoichiometric combinations of a,x-aminopropyl terminated polydimethylsiloxane (PDMS) oligomers with number average molecular weights ranging from 700 to 15,000 g/mole and bis(4-isocyanatocyclohexyl)methane (HMDI).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…For instance, Adhikari et al reported that incorporation of 40 mol% of the disiloxane-based chain extenders 1,3-bis(4-hydroxybutyl) and (3-hydroxypropyl)-tetramethyldisiloxane along with 1,4-butanediol increased the solubilities of the HSs in the PDMS/PHMO soft phases [ 61 , 62 ]. Yildirim et al simulated the morphology of segmented aliphatic silicone-urea copolymers with varying HS contents using DPD calculations [ 63 ]. Models for PSU copolymers revealed a microphase separated morphology even at the very low HS content of 1.7%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Adhikari et al reported that incorporation of 40 mol% of the disiloxane-based chain extenders 1,3-bis(4-hydroxybutyl) and (3-hydroxypropyl)-tetramethyldisiloxane along with 1,4-butanediol increased the solubilities of the HSs in the PDMS/PHMO soft phases [ 61 , 62 ]. Yildirim et al simulated the morphology of segmented aliphatic silicone-urea copolymers with varying HS contents using DPD calculations [ 63 ]. Models for PSU copolymers revealed a microphase separated morphology even at the very low HS content of 1.7%.…”
Section: Resultsmentioning
confidence: 99%
“…Models for PSU copolymers revealed a microphase separated morphology even at the very low HS content of 1.7%. When the HS content was increased by decreasing the PDMS molecular weight, the morphology changed from spherical randomly dispersed hard domains to large ribbon-like crystalline hard domains that became interpenetrating, particularly at high urea HS contents [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, ultimate tensile strengths of silicone-urea copolymers showed a linear dependence on the urea hard segment content, as reproduced inFigure 16(89). Molecular dynamics and mesoscale dynamics simulation studies were also used to study the morphology and properties of silicone-urea copolymers with PDMS segment lengths varying between 700 and 15,000 g/mol and urea hard segment content between 1.7 and 34% by weight(98). Results clearly indicated the presence of well microphase separated morphologies and very strong bidentate hydrogen bonding between urea hard segments, leading to the formation of strong elastomers.…”
mentioning
confidence: 85%
“…and Wilkes(91)(92)(93)(94)(95)(96)(97)(98), Runt(88, 99- 102)and Gunatillake(87,(103)(104)(105)(106)(107) have been very active regarding the preparation, characterization and investigation of the structure-morphology-property behavior of siliconeurea and silicone-urethane copolymers.Webster and co-workers(84)(85)(86)(108)(109)(110)(111)(112)(113)(114)(115)(116)have mainly investigated the synthesis and characterization of silicone containing crosslinked polyurethane networks and their performance as antifouling or foul release coatings. A comprehensive investigationon the effect of a large number of variables, including PDMS molecular weight, type and structure of the diisocyanate and the chain extender and hard/soft segment content, on the structure-morphology-property behavior of homologous siliconeurethane and silicone-urea copolymerswas performed(89, 91-98, 117).…”
mentioning
confidence: 99%
“…In order to better understand the effect of diisocyanate chain symmetry on the nature of hydrogen bonding between urea and urethane groups in the molecular level, quantum mechanical calculations (QMC) and molecular dynamic simulations (MD) were performed [12,55]. As shown in Figure 11, these studies clearly showed the dramatic effect of chain symmetry in PPDI-PTMO1k urethane on the formation of a wellordered and strongly hydrogen bonded urethane hard segment network.…”
Section: Influence Of Hydrogen Bonding and Diisocyanate Symmetry On Tmentioning
confidence: 99%